2004
DOI: 10.1002/ajmg.c.30027
|View full text |Cite
|
Sign up to set email alerts
|

Unravelling the genetics of prostate cancer

Abstract: This review describes what is currently known about the genetics of prostate cancer. Traditionally, the genetics of a suspected inherited cancer predisposition have generally been thought of in terms of a single, high-risk gene with a dominant mode of inheritance. Such a gene might be observed in families, as has been documented in familial breast cancer (BRCA1/2), familial colorectal cancer (HNPCC), retinoblastoma (RB1), and Wilms tumor (WT1). This review investigates the evidence for the existence, first of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
43
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 94 publications
0
43
0
Order By: Relevance
“…Although empirical data are available to counsel men about their risk based on family history, 24 providing information about the genetics of prostate cancer is less straightforward because the molecular basis of hereditary prostate cancer predisposition is poorly understood. 13 Still, there may be benefit in responding to misconceptions held by these men about the effect of (hypothetical) genetic testing on health outcomes (Ruth Cowan, BSc, unpublished data) and to lay beliefs about inheritance that are commonly held by families with inherited conditions. 39,40 Although items relating to counseling and peer support were the least endorsed by respondents, approximately half of the respondents did indicate some level of interest in each of these services, and the majority indicated they had not had any or enough support in relation to their family history.…”
Section: Sample Considerationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although empirical data are available to counsel men about their risk based on family history, 24 providing information about the genetics of prostate cancer is less straightforward because the molecular basis of hereditary prostate cancer predisposition is poorly understood. 13 Still, there may be benefit in responding to misconceptions held by these men about the effect of (hypothetical) genetic testing on health outcomes (Ruth Cowan, BSc, unpublished data) and to lay beliefs about inheritance that are commonly held by families with inherited conditions. 39,40 Although items relating to counseling and peer support were the least endorsed by respondents, approximately half of the respondents did indicate some level of interest in each of these services, and the majority indicated they had not had any or enough support in relation to their family history.…”
Section: Sample Considerationsmentioning
confidence: 99%
“…12 Nonetheless, the molecular basis of susceptibility remains unclear. 13 Currently, it is uncommon for men with a family history suggestive of hereditary prostate cancer to be seen in cancer genetics clinics. In Australia and possibly other countries, this may be due in part to the minimal guidelines for screening or referral of men with a family history of prostate cancer to cancer genetic services.…”
mentioning
confidence: 99%
“…Excluding advanced age and African-American ancestries, the strongest risk factor for the disease is a family history of PCa. [4][5][6] PCa is one of the common cancers with a large genetic component, as up to 42% of the risk could be explained by inheritance from studies about twins. 7 Genome-wide association studies (GWAs) have identified 46 susceptibility loci associated with PCa [8][9][10][11][12][13][14][15][16][17][18][19][20] that individually contribute to a small increase in PCa risk, but which taken together, could explain more than 25% of the excess of PCa familial risk.…”
Section: Introductionmentioning
confidence: 99%
“…Higher risks have been shown for men with two or more affected relatives. [4][5][6][7][37][38][39][40] This increase is too great to be explained by non-genetic factors alone. Analyses based on the Nordic twin registries have found higher risks in monozygotic than dizygotic twins, supporting the hypothesis that much of this familial aggregation is due to genetic factors (42%), rather than shared lifestyle factors.…”
Section: Introductionmentioning
confidence: 99%
“…Younger ages at diagnosis and multiple affected relatives with the disease tend to be associated with even higher relative risk (2). The disease has a complex etiology, with genetic studies suggesting that multiple genes are important in the onset, progression, and treatment response (9)(10)(11)(12)(13)(14).…”
Section: Introductionmentioning
confidence: 99%